1999
DOI: 10.1097/00003072-199905000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 Fluorodeoxyglucose Splenic Uptake From Extramedullary Hematopoiesis After Granulocyte Colony-stimulating Factor Stimulation

Abstract: Two patients with sarcoma, one with recurrent osteosarcoma of the spine and the other with metastatic synovial cell sarcoma, were treated with high-dose chemotherapy that produced severe leukopenia. The patients received granulocyte colony-stimulating factor (G-CSF) to stimulate the bone marrow (480 mg given subcutaneously twice daily for 5 to 7 days); their responses were seen as a marked increase in peripheral leukocyte count with no change in the erythrocyte or platelet counts. The patients had fluorine-18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…However, myelopoiesis also contributes to the observed bone marrow signal [30], and the exact contribution of each process cannot be estimated from the results of this study. Nevertheless, the observed results indicate that 18 F-FDG PET/CT may become a promising technique for the quantitation of bone marrow involvement…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, myelopoiesis also contributes to the observed bone marrow signal [30], and the exact contribution of each process cannot be estimated from the results of this study. Nevertheless, the observed results indicate that 18 F-FDG PET/CT may become a promising technique for the quantitation of bone marrow involvement…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, 18 F-FDG PET/CT is widely used for evaluation of inflammatory diseases based on increased glucose metabolism in inflammatory processes [27,29]. EMH may exhibit increased 18 F-FDG uptake [30]. Early and robust inflammation is a hallmark of myelofibrosis pathophysiology, and may be a target for PET imaging.…”
mentioning
confidence: 99%
“…[1][2][3] Hematopoietic cytokines, such as granulocyte colony-stimulating factor (G-CSF) and granulocytemacrophage colony-stimulating factor cause increased FDG uptake in the bone marrow 4 and in the spleen. 5,6 In animal experiments, it has been shown that FDG activity in bone marrow continues to be elevated as long as 4 weeks after completion of G-CSF, and the elevated marrow FDG uptake was sustained longer than the period of blood neutrophil count elevation. 7 Hematopoietic cytokine-induced bone marrow FDG uptake is often diffuse.…”
mentioning
confidence: 99%
“…Since the spleen is an active site for the extramedullary hematopoesis, a diffuse spleen enhancement of 18 F-FDG uptake represents in patients receiving hematopoietic growth factor (HGF), such as granulocyte colony stimulating factor (G-CSF) and erythropoietin [20,21].…”
Section: Gastrointestinal Tractmentioning
confidence: 99%
“…An increased diffuse 18 F-FDG activity in the bone marrow may be seen also in the patients receiving HGF such as erythropoietin, G-CSF, and granulocyte macrophage colony-stimulating factor (GM-CSF) [20,21,25].…”
Section: Therapy Related Artifactsmentioning
confidence: 99%